Bioresources of Wild Medicinal Plants in Canyons Gulobod and Saphedchashma (Gissar Ridge, Tajikistan) - Saidovich Sattarov, Jamshed; Khadjibukarovich Vyshegurov, Sultan; Safarovich Murodov, Shamsulom; Raifovich Galeev, Rinat; Sergeevich Samarin, Ivan (International Journal of Engineering and Technology, 2018)
The results of assessing the biodiversity and resources of wild plants on the territory of Gulobod and Saphedchashma canyons in the Hissar Mountains of Tajikistan have been presented. In the territory of the Gulobod canyon, 79 various species of medicinal plants have been identified. Out of these, three plants are listed in the Red Book of the Republic, eight are endemic ones, and four are adventive plants. Out of the studied 15 vegetation beds, commercial ones were 7, which were formed by horseheal – Inula helenium L.- and small-flowered oregano – Origanum tyttanthum Gontsch., the total area of which reached 3.3 ha. In the territory of the Saphedchashma canyon, 50 most common medicinal plants had been identified, formed by representatives of 38 species belonging to 17 various families.